Gastric-type endocervical adenocarcinoma, superficial myofibroblastoma, sex cord-stromal tumors, and HSIL in Peutz−Jeghers syndrome: a rare case report, genetic characterization, and review of literature - Sun, Dongjin; Li, Yumei; Cao, Zhixing (Frontiers in Oncology, 2025)
Peutz-Jeghers syndrome (PJS) is characterized by an increased risk of gynecologic tumors. Gastric-type endocervical adenocarcinoma (GEA) is a rare non-human papillomavirus (HPV)-related tumor. We reported an uncommon case of a 39-year-old woman with PJS who developed GEA, superficial cervical vaginal myofibroblastoma, sex cord-stromal tumors with annular tubules of the ovaries, and cervical and vaginal high-grade squamous interepithelial neoplasia (HSIL). Before being verified GEA, the patient had been experiencing suspicious symptoms for over 9 years, with nabothian cysts and vaginitis being misdiagnosed. HSIL displayed widespread p16 immunostaining, and HPV DNA screening confirmed HPV-18 infection, although GEA was negative. Further, we verified TP53 mutation and HER2 amplification of GEA by fluorescence in situ hybridization (FISH). TP53 was the most commonly mutated gene. The therapy with the anti-HER2 antibody trastuzumab was suggested based on HER2 amplification. We also analyzed the somatic mutations of GEA by whole genome sequencing (WES). There were 157 single nucleotide variations (SNVs) and 215 indels, with all of them being heterozygotes. Nonsynonymous and frameshift insertions were the most common kinds of mutations. The germine STK11 gene mutation was found, which may play an important role in tumor development. According to gene function enrichment analyses, the genomic changes primarily implicated general transcription or expression pathways and cell cycle pathways. In addition, the JAK2/STAT3 pathway could be a major focus of targeted therapy for GEA patients with PJS. Our findings show that the patient with PJS can have a variety of unusual gynecologic tumors. Patients with PJS must have routine gynecological, ultrasonographic, and cytological examinations to detect precursor or early-stage lesions. The patient’s abnormal symptoms must be treated early with caution. A comprehensive genomic study reveals the potential causative genetic factors, therapeutic targets, and chemotherapy resistance of GEA. Further research will focus on the main driving genes, molecular mechanisms, and molecular target therapy in more patients.